Muhammad Yusuf Faruqi. Early Islamic Lego-Political Institutions: An Exploratory Study - Amin, Shams Ul Haq (Islamic Studies, 2017)
Muhammad Yusuf Faruqi. Early Islamic Lego-Political Institutions: An Exploratory Study